2011
DOI: 10.1371/journal.pone.0020127
|View full text |Cite
|
Sign up to set email alerts
|

CovR-Controlled Global Regulation of Gene Expression in Streptococcus mutans

Abstract: CovR/S is a two-component signal transduction system (TCS) that controls the expression of various virulence related genes in many streptococci. However, in the dental pathogen Streptococcus mutans, the response regulator CovR appears to be an orphan since the cognate sensor kinase CovS is absent. In this study, we explored the global transcriptional regulation by CovR in S. mutans. Comparison of the transcriptome profiles of the wild-type strain UA159 with its isogenic covR deleted strain IBS10 indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 59 publications
2
49
0
Order By: Relevance
“…The overlap includes genes for cell-wall division and biofilm formation ( gbpB , lysM, gtfB , gtfC ), with VicR positively regulating these genes and CovR acting as a repressor [107,141,142]. In EMSA assays, it was observed that VicR Sm VicR and CovR co-bind the promoter regions of lysM , gbpB , and gtfC [107].…”
Section: Interactions Of Vicrk Tcs With Other Regulatory Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…The overlap includes genes for cell-wall division and biofilm formation ( gbpB , lysM, gtfB , gtfC ), with VicR positively regulating these genes and CovR acting as a repressor [107,141,142]. In EMSA assays, it was observed that VicR Sm VicR and CovR co-bind the promoter regions of lysM , gbpB , and gtfC [107].…”
Section: Interactions Of Vicrk Tcs With Other Regulatory Systemsmentioning
confidence: 99%
“…In S. mutans , the system was originally designated GcrR (for glucan-binding protein C regulator) following identification in a screen for genes that regulate aggregation between GbpC and dextran [161]. Later studies revealed that CovR Sm negatively or positively regulates about 6.5% of the S. mutans genome [142]. More importantly, CovR Sm directly represses a panel of genes required for the synthesis of water-soluble and water-insoluble glucan ( gtfB , gtfC ) and other exopolysaccharides derived or not from sucrose ( epsC and ftf ), as well as surface proteins GbpC and GbpB that bind to glucan [107,141,142].…”
Section: Tcs Covrs and Covr As An Orphan Regulatormentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous study in our lab using whole-genome microarray analysis, we have shown that in S. mutans, CovR differentially regulates approximately 6.5% of the genes (25), where it acts both as an activator and a repressor. CovR represses half of these genes, including gtfB (glucosyltransferase B), gtfC (glucosyltransferase C), and gbpC (glucan-binding protein C).…”
mentioning
confidence: 88%